Local mechanical stimulation induces components of the pathogen defense response in parsley - Gus-Mayer, Sabine (The National Academy of Sciences, 1998)
Cell suspension cultures of parsley (Petroselinum crispum) have previously been used as a suitable system for studies of the nonhost resistance response to Phytophthora sojae. In this study, we replaced the penetrating fungus by local mechanical stimulation by using a needle of the same diameter as a fungal hypha, by local application of a structurally defined fungus-derived elicitor, or by a combination of the two stimuli. Similar to the fungal infection hypha, the local mechanical stimulus alone induced the translocation of cytoplasm and nucleus to the site of stimulation, the generation of intracellular reactive oxygen intermediates (ROI), and the expression of some, but not all, elicitor-responsive genes. When the elicitor was applied locally to the cell surface without mechanical stimulation, intracellular ROI also accumulated rapidly, but morphological changes were not detected. A combination of the mechanical stimulus with simultaneous application of low doses of elicitor closely simulated early reactions to fungal infection, including cytoplasmic aggregation, nuclear migration, and ROI accumulation. By contrast, cytoplasmic rearrangements were impaired at high elicitor concentrations. Neither papilla formation nor hypersensitive cell death occurred under the conditions tested. These results suggest that mechanical stimulation by the invading fungus is responsible for the observed intracellular rearrangements and may trigger some of the previously demonstrated changes in the activity of elicitor-responsive genes, whereas chemical stimulation is required for additional biochemical processes. As yet unidentified signals may be involved in papilla formation and hypersensitive cell death.